Disentangling the effects of attentional difficulties on fears of social evaluation and social anxiety symptoms: Unique interactions with sluggish cognitive tempo - Fredrick, Joseph W. (J Psychiatr Res, 2020)
Although fears of negative and positive social evaluation are hallmark cognitive features of social anxiety, attentional difficulties may exacerbate the relation between fears of social evaluation and social anxiety. Thus, the goal of the current study was to test whether two different types of self-reported attentional difficulties, specifically sluggish cognitive tempo (SCT) and attention-deficit/hyperactivity disorder (ADHD) inattention symptoms, moderate the relation between fears of social evaluation and social anxiety. Participants (N = 4,756; Mage = 19.28 years; 72.7% female) enrolled in five universities across the United States completed self-report measures of fears of negative and positive evaluation and psychopathology symptoms. Results indicated a significant two-way interaction of fear of negative evaluation and SCT in relation to social anxiety symptoms, as well as a significant two-way interaction of fear of positive evaluation and SCT in relation to social anxiety symptoms. In both instances, the associations between fears of negative and positive evaluation in relation to social anxiety became increasingly stronger at higher levels of SCT. Conversely, the interactions between fears of negative and positive evaluation with ADHD inattentive symptoms were non-significant. These results are the first to report that self-reported SCT, but not ADHD inattentive symptoms, exacerbate the relation between fears of social evaluation and social anxiety, and suggest that attentional difficulties characteristic of SCT may prolong engagement in fears.